Youth: perspectives of high school teachers and students (Research, Society and Development, 2023)
How to think about youth today? What are your features? The purpose of this article is to discuss the issue of youth from the perspective of teachers and high school students in a state public school in Cascavel/PR. Initially, the metamorphoses from modern to post-modern values are highlighted, in order to, in a second moment, focus on the characteristics of the new generations and their youth groupings. Based on the theoretical-methodological framework of the sociology of everyday life by Michel Maffesoli, data from a field survey carried out with the aim of apprehending, through interviews, the observed youth of teachers and students are analyzed. Such results pointed towards a coexistence of modern and postmodern values and the need to think about pedagogical alternatives and the manifestation of new ways of becoming young in postmodernity.